Audit committee reporting: current practices of companies listed on the Kuala Lumpur stock exchange (Bursa Malaysia) - Muhamad Sori, Zulkarnain; Ramadilli Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This study examines the disclosures contained in Audit Committee Reports (ACRs) and the level of compliance of current practices with the amended Kuala Lumpur Stock Exchange listing requirements after the adoption of various recommendations made by the High-Level of Finance Committee on Corporate Governance and the Malaysian Code on Corporate Governance (MCCG) in 1999 and 2000 respectively. All firms listed on the KLSE’s main and second board, and MESDAQ counters were sampled. Consistent with the literature in developed markets, the findings reveal that very few companies provide more than what is expected by the ACRs in their listing requirements. Further, companies in finance, technology and IPC counters, and companies on the main board counter have greater initiative to provide value added (or termed as ‘non-boiler plate’) statements to information users.